Development of Low Profile Cavity Backed Crossed Slot Antennas for Planar Integration - Luo, Guo Qing; Hu, Zhi Fang; Liang, Yaping; Yu, Li Yang; Sun, Ling Ling (IEEE transactions on antennas and propagation, 2009)
Single fed low profile cavity backed crossed slot antennas for dual frequency dual linear polarization and circular polarization applications are first presented in this paper. By employing the substrate integrated waveguide (SIW) technique in the antenna designs, the low profile backed cavity structure can be realized by using only a single layer of low cost printed circuit board (PCB) substrate. A single grounded coplanar waveguide (GCPW) is employed as the feeding element to excite the TE 120 and TE 210 modes in the SIW cavity. A crossed slot structure is used as the radiating element in order to radiate the desired dual linearly or circularly polarized wave. From the measurement results, it is seen that these novel antennas retain the advantages of conventional metallic cavity backed antennas, including high gain, high front-to-back ratio (FTBR), and low cross polarization level (CPL). Furthermore, the proposed antennas also possess the advantages of low profile, light weight, low fabrication cost, and easy integration with planar circuits.